A PCR-Based Technique to Track the Geographic Origin of Plasmodium falciparum With 23-SNP Barcode Analysis - Hu, Fengyue; Zou, Qicheng; Li, Yinyue; Zhu, Guoding; Zhou, Huayun; Zhang, Meihua; Tian, Fang; Liu, Yaobao; Lu, Feng (Frontiers in Public Health, 2021)
Increased population movement has increased the risk of reintroducing parasites to elimination areas and also dispersing drug-resistant parasites to new regions. Therefore, reliable and repeatable methods to trace back to the source of imported infections are essential. The recently developed 23-single-nucleotide polymorphism (SNP) barcode from organellar genomes of mitochondrion (mt) and apicoplast (apico) provides a valuable tool to locate the geographic origin of Plasmodium falciparum. This study aims to explore the feasibility of using the 23-SNP barcode for tracking P. falciparum by polymerase chain reaction and sequencing, while providing geographical haplotypes of isolates that originated from Central Africa. Based on 23-SNP barcode analysis, SNPs were found at seven loci; 27 isolates were confirmed to have originated in West Africa, and this study also showed four isolates from Central Africa (Equatorial Guinea, 3; Republic of Congo, 1) that originated in East Africa. This study provides the sequence data from Central Africa and fills 23-SNP barcode data gaps of sample origins.